KEEFEKTIFAN MEDIA PEMBELAJARAN EDUCAPLAY PADA MATA PELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - Hilma Ayu Alfanisa; Rudi Umar Susanto; Syamsul Ghufron; Nafiah, Nafiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students in the Indonesian language subject, particularly on the material of intrinsic elements of narrative texts. The purpose of this study was to examine the effectiveness of Educaplay as a learning media on the learning outcomes of fourth-grade students at SD Iskandar Said Surabaya. This research employed a quantitative approach with a Pre-Experimental Design using a one-group pretest-posttest type. The research sample consisted of 22 students from class IV-B. The research instrument was a multiple-choice test consisting of 10 questions administered for both the pretest and posttest. The pretest results showed that only 4.5% of students achieved the Minimum Mastery Criterion (KKM), with a class average score of 60.45. After the implementation of the Educaplay learning media, the posttest results indicated a significant improvement, with 90.9% of students successfully exceeding the KKM and the average score increasing to 88.64. The N-Gain analysis showed an average score of 0.74, which falls into the high category. Therefore, the Educaplay learning media was proven to be effective in improving Indonesian language learning outcomes of fourth-grade students at SD Iskandar Said Surabaya.